The Euroschool Lectures on Physics with Exotic Beams, Vol. III - Al-Khalili, J.S.; Roeckl, E.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This is the third volume in a series of Lecture Notes based on the highly successful Euro Summer School on Exotic Beams. The aim of these notes is to provide a thorough introduction to radioactive ion-beam physics at the level of graduate students and young postdocs starting out in the field. Each volume covers a range of topics from nuclear theory to experiment and applications. Vol I has been published as LNP 651, ISBN 978-3-540-22399-3; Vol II has been published as LNP 700, ISBN 978-3-540-33786-7.
Shell Structure of Exotic Nuclei -- Testing the Structure of Exotic Nuclei via Coulomb Excitation of Radioactive Ion Beams at Intermediate Energies -- Test of Isospin Symmetryisospin symmetry Along the N=Z Line -- Beta Decay of Exotic Nuclei -- One- and Two-Proton Radioactivity -- Superheavy Elements -- Experimental Tools for Nuclear Astrophysics.
Keywords: Physics; Astrophysics; Nuclear physics; Heavy ions; Hadrons; Physical measurements; Measurement; Physics; Nuclear Physics, Heavy Ions, Hadrons; Astrophysics and Astroparticles; Measurement Science and Instrumentation; Electronic books